Levels of IL-6 and TNF-α among Type 2 Diabetic Patients with Dyslipidemia and Insulin Resistance - Najlaa Jabaar Wasmi (Journal of Global Pharma Technology, 2018)
This study was aimed to investigate the effect of type2 diabetes mellitus in Iraqi male patients on the levels of IL-6 and TNF-α and their relationship with IR and dyslipidemia. The study included (80) individual (males), (60) were diagnosed with type2 diabetic patients and (20) as healthy control group.IL-6 and TNF-α biomarkers were assessed in both control and diabetic groups. Results showed increasing levels of IL-6 in diabetic group ((9.065 ± 0.504) in comparison with healthy control group (4.186 ± 0.509), TNF-α was increased significantly (p<0.05) in diabetic group (44.222 ± 7.336) in comparison with control group (11.082 ± 1.204). FBG level was increased significantly (p < 0.01) in diabetic groups (233.90±11.12) in comparison with control group (92.90±240).HbA1cin diabetic group (7.59 ± 0.21) showed significant increase (p < 0.01) in comparison with control group (4.59 ± 0.11).Insulin showed high significant (p < 0.01) increase in diabetic group (18.24 ± 2.27) when compared with control group (6.74 ± 0.86).IR value was increased significantly (p < 0.01) in diabetic group (11.58 ± 1.89) when compared with control group (1.56 ± 0.21).Total cholesterol showed non- significant (p> 0.05) difference in diabetic group (188.83 ± 5.46) in comparison with control group (186.40 ± 7.47). Triglycerides value was increased significantly (p < 0.01) in diabetic group (208.05 ± 11.41) when compared with control group (125.55 ± 11.18).LDL showed non-significant (p> 0.05) difference in diabetic group (102.23 ± 4.29) in comparison with control group (111.85 ± 7.24).VLDL was increased significantly (p < 0.01) in diabetic group (41.95 ± 2.33) when compared with control group (23.99 ± 2.47).HDL showed non-significant difference (p> 0.05) in diabetic group (47.15 ± 1.15) in comparison with control group (50.46 ± 1.86).Key words: IL-6, TNF-α, Diabetes type2, insulin resistance (IR), Dyslipidemia.